2008
DOI: 10.1007/s12275-007-0167-7
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial characteristics of Curcuma xanthorrhiza extract on Streptococcus mutans biofilm

Abstract: This study evaluated the antibacterial effects of a natural Curcuma xanthorrhiza extract (Xan) on a Streptococcus mutans biofilm by examining the bactericidal activity, inhibition of acidogenesis and morphological alteration. Xan was obtained from the roots of a medicinal plant in Indonesia, which has shown selective antibacterial effects on planktonic S. mutans. S. mutans biofilms were formed on slide glass over a 72 h period and treated with the following compounds for 5, 30, and 60 min: saline, 1% DMSO, 2 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 23 publications
3
43
0
Order By: Relevance
“…The length of exposure was based on previous studies that stated that the maximal bacteria inhibition effect of antibacterial agents requires exposure to the antibacterial agent for 60 minutes [21].…”
Section: Discussionmentioning
confidence: 99%
“…The length of exposure was based on previous studies that stated that the maximal bacteria inhibition effect of antibacterial agents requires exposure to the antibacterial agent for 60 minutes [21].…”
Section: Discussionmentioning
confidence: 99%
“…1 Previous studies reported that 0.2% chlorhexidine gluconate has shown to inhibit Streptococcus mutans counts very effectively in contaminated toothbrushes. 1,10,[12][13][14]19,28,29 …”
Section: Effectiveness Of Antimicrobial Solutions On Streptococcus Mumentioning
confidence: 99%
“…As it has no outer layer, antimicrobial agents can permeate the S. mutans cell wall and cause biosynthesis disturbance. The hydroxyl group in the Xan contained in ethanoltemulawak extract contributes to antimicrobial activity by inducing cell wall protein denaturation; the protein of the cell leaks out and causes cell death [10,4]. In the Gram-negative A. actinomycetemcomitans; however, the outer layer consists of lipopolysaccharide, lipoprotein, and periplasm bound to peptidoglycan.…”
Section: Discussionmentioning
confidence: 99%
“…It is now proved that ethanol-temulawak extract can prevent S. mutans biofilm formation, but not as effectively as CHX. The ethanol-temulawak extract works by disrupting cell wall integrity, causing lysis with disruption of the cell wall and membrane, and thus, destroying the ability of S. mutans to adhere and form a biofilm [11,4]. The effect of ethanoltemulawak extract against A. actinomycetemcomitans biofilm formation was determined in the same way as for S. mutans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation